ASSESSMENT OF THE AIRWAYS ON A LATERAL HEAD CEPHALOMETRIC RADIOGRAPHS - Кобцева, Олена (SWorldJournal, 2024)
Oral breathing is a common functional pathology among orthodontic patients. Chronic nasal congestion triggers a number of mechanisms that seriously disrupt the structure of the face, jaws, and tooth positioning and lead to the development of obstructive